2019
DOI: 10.1016/j.jvscit.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Vertebroplasty-associated cement leak leading to iatrogenic venous compression and thrombosis

Abstract: A 91-year-old woman presented with left lower extremity swelling and pain diagnosed as phlegmasia cerulea dolens. Doppler ultrasound and venography revealed extensive left lower extremity deep venous thrombosis. Review of prior images revealed cement leakage causing compression of the left common iliac vein. She underwent successful mechanical thrombectomy using the ClotTriever device (Inari Medical, Irvine, Calif) and subsequent stent placement. Phlegmasia cerulea dolens resolved on the following day, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…6 Nezami et al described a patient who developed PCD as a result of vertebroplasty-associated cement leakage, and was treated with PT. 7 Another case report presented a patient who developed PCD due to an external compression of the iliofemoral venous axis by a hematoma which resulted from shearing of a sacral screw placed during a spinal fusion surgery. 8 Our analysis revealed that three patients developed PCD following a spinal surgery which raises a concern whether vertebral instrumentation and spinal fusion surgeries can carry the risk of direct external compression of the iliofemoral venous axis, placing these individuals at a high risk for developing fulminant DVT's that have the potential for progressing to PCD.…”
Section: Discussionmentioning
confidence: 99%
“…6 Nezami et al described a patient who developed PCD as a result of vertebroplasty-associated cement leakage, and was treated with PT. 7 Another case report presented a patient who developed PCD due to an external compression of the iliofemoral venous axis by a hematoma which resulted from shearing of a sacral screw placed during a spinal fusion surgery. 8 Our analysis revealed that three patients developed PCD following a spinal surgery which raises a concern whether vertebral instrumentation and spinal fusion surgeries can carry the risk of direct external compression of the iliofemoral venous axis, placing these individuals at a high risk for developing fulminant DVT's that have the potential for progressing to PCD.…”
Section: Discussionmentioning
confidence: 99%
“…The literature also described a few more cases where the ClotTriever system was successfully used for DVT. In one case study, it was used as an adjunct to CDT [ 6 ], and in two other cases, it was used as the sole treatment, one for a patient with extensive DVT [ 7 ] and another for a patient with PCD [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the common complications of PVP include bone cement leakage, cement embolism, intraoperative puncture injury and new fractures ( 8 11 ). Bone cement leakage and embolism may cause serious adverse complications, such as pulmonary cement embolism ( 12 15 ), spinal compression ( 16 , 17 ), neurological deficit ( 18 , 19 ), atrial mass cement embolism ( 20 ), and iatrogenic venous compression ( 21 ), which have attracted a lot of attention. However, there are few reports about the hemorrhage caused by vascular injury, although the bleeding may lead to shock or other serious and terrible complications.…”
Section: Introductionmentioning
confidence: 99%